Frequency of H. pylori in liver cirrhosis patients with overt Hepatic encephalopathy at tertiary care hospital, Karachi. - Shaista Ahmed; Siddiqui, Afshan; Sadia Iqbal; Rma Waqas; Jamal Ara; Kidwai, Aneela Altaf (International Journal of Endorsing Health Science Research, 2022)
Background: Ammonia is detoxified in the liver, and hepatic insufficiency due to cirrhosis leads to raised ammonia, causing symptoms of Hepatic Encephalopathy (HE). Studies proclaim that Helicobacter pylori (H. pylori) accelerate ammonia production. The study objective was to establish the frequency of H. pylori in liver cirrhosis patients with overt HE. Methodology: This cross-sectional study was conducted in Medical Unit-I Abbasi Shaheed Hospital, Karachi, from May to November 2018. Liver Cirrhosis patients between the ages of 31-60 years were selected via non-probability sampling. Patients of any sex suffering from liver cirrhosis for six months, as proved by ultrasound and overt HE diagnosed using West Haven Criteria, were included in the study. Stool samples were collected from patients in a sterile manner. Results of stool for H. pylori antigen were recorded. Data were analyzed using SPSS version 16.0. Results: Out of 135 patients with Liver Cirrhosis with overt HE, 42 (31.1%) suffered from H. pylori infection while 93 (68.9%) patients did not. The mean age of patients was 44.14 ± 8.49 years. Stratification of the age of patients with H. pylori infection showed significant results (p=0.00). The mean disease duration was 4.72 ± 1.24 years. Stratification based on disease duration with H. pylori infection revealed significant results (p=0.00). Stratified findings based on Child-Pugh classification and H. pylori infection were insignificant (p=0.50). Conclusion: Our study reveals there is less frequency of H. pylori infection amongst liver cirrhotic patients. However, amongst those infected, many had a longer duration of disease. Our study indicates more cases of H. pylori infection with increasing age of liver cirrhosis patients. Furthermore, the relation between H. pylori infection and the Child-Pugh classification indicates that overt HE may be attributed to factors other than H. pylori infection.